Microcomputers and electronic instrumentation : making the right connections. - Malmstadt, Howard V.; Enke, Christie G.; Crouch, Stanley R. (Washington, United States of America : American Chemical Society, 1994)
"The authors believe that the effectiveness of future generations of scientists depends in part on their ability to use intelligently, diagnose, and modify their microcomputer-based and electronic instrumentation. Using a "top-down" approach, the authors present electronic concepts, principles, and technology that are impacting our daily lives. They start at the top, by providing a broad perspective of electronic instrumentation, and work down to functional modules, devices, and detailed operations. This top-down approach enables all of the pieces to fit together so that a working knowledge is developed as one proceeds through the chapters. Written specifically for chemists, physicists, engineers, biologists, medical researchers, students, and other technical personnel who can benefit from "making the right connections" to modern instrumentation, this book will empower you to gain better control and make better use of your microcomputers and laboratory instruments." (Copied from the paste).
Preface. About the authors. Chapter 1. Connecting to the new wave of microcomputer instrumentation. Chapter 2. Converting and acquiring data scientific instrumentation. Chapter 3. Understanding and measuring analog signals. Chapter 4. Supplying power to instruments and computers. Chapter 5. Manipulating analog data with operational amplifiers and servo systems. Chapter 6. Thinking digital: logic gates, flip-flops, and counters. Chapter 7. Generating, switching, and processing analog signals. Chapter 8. Sensing and controlling in automation and robotics. Chapter 9. Getting the most from real-world signals. Chapter 10. Troubleshooting your instruments. Supplement 1. Generating and controlling analog electrical quantities. Supplement 2. Describing waveforms and reactive circuits. Supplement 3. Understanding diodes, transistors, and other solid-state devices. Appendix A. Grounding and shielding. Appendix B. Components. Appendix C. Digital data transmission. Index.
Keywords: ELECTRONIC INSTRUMENTS; COMPUTER INTERFACES; MICROCOMPUTERS; AUTOMATIC DATA COLLECTION SYSTEMS